Quality Control In Kompas/Kompas.Id Daily News Production - Nasrullah Nasrullah; Veronika Veronika; Rossalyn Ayu Asmarantika (ULTIMA Comm, 2024)
Abstract In the digital era, marked by the rapid production of news, the phenomenon of misinformation has become an increasingly difficult challenge to avoid. Consequently, the gatekeeping function remains highly relevant to ensure that mass media does not fall into the trend of disseminating news that fails to meet journalistic standards due to the pressure of rapid publication. Responding to the developments of the time and changes in public consumption patterns, Harian Kompas, initially a print medium, has transformed since 2017 into the digital platform Kompas.id. This study aims to examine how gatekeeping functions within Harian Kompas/Kompas.id in the context of news production quality control (QC), using a documentation study approach. The QC function at Harian Kompas/Kompas.id is managed by the Editing and Language Harmonization Department, where the lead author has been actively involved over the past four years. This function is not only applied prior to publication but also to content that has already been published. This reflects the dynamic nature of the newsroom, extending into the public sphere, while also demonstrating an ethos to avoid errors in reporting. The QC function supports the editor-in-chief in safeguarding the realization of quality and enlightening journalism through both substantive and linguistic editing.